Peran Pembiayaan Murabahah Dalam Pengembangan Kinerja Usaha Mikro Pada Baitul Maal Wat Tamwil (BMT) UB Amanah Syariah Laut Dendang - Suherti Nur Elyana; Mutiah Khaira Sihotang (Universitas Labuhanbatu, 2023)
With the development of the times, the quality of education has become a necessity and is required to be able to fulfill everything required by each institution in the education unit. The learning process is said to be successful if all aspects of learning can support each other to create a conducive situation in the learning activity so that the learning objectives can be achieved. achieved optimally. The research approach used is a qualitative approach. A qualitative approach is defined as a research approach that asks questions and procedures in collecting data from participants, analyzing data and interpreting data. This research was conducted at MTs PN 4 Medan on Jalan Raya Besar, kec. Medan Labuhan, Medan City, North Sumatra. Based on the results of the research that has been carried out, it can be concluded that learning Islamic Religious Education, Islamic Cultural History Subjects, uses the Image Media-Based Team Teaching Model to Improve Student Learning Activities at MTs PN 4 Medan.